RETÍCULO PERICARDITE TRAUMÁTICA EM BOVINO DE LEITE: RELATO DE CASO - TESCH , JOICE; NUNES DOS SANTOS , EDUARDA; RIBEIRO VIANA MARTINS , LUCIANE; TEIXEIRA LINHARES , MARCELLA; PERLIN DOS SANTOS , GABRIELA (Salão do Conhecimento, 2020)
Relato de caso de uma propriedade rural